Battery Ingestion with Colonic Perforation after Colostomy Closure in a Toddler - Lukish, Annamarie C.; Pat, Vivien; Apte, Anisha; Levitt, Marc A. (European Journal of Pediatric Surgery Reports, 2022)
Disc and button battery ingestion in children is common. In fact, data reports a dramatic increase in battery ingestion during the coronavirus disease 2019 pandemic likely as a result of increased household population density and electronic product utilization. These batteries often remain lodged in the esophagus causing potentially devastating complications if they are not removed urgently. Batteries that are passed beyond the esophagus usually do not cause any complications. We present the case of a 15-month-old male who underwent a colostomy takedown 2 months following a posterior sagittal anorectoplasty for imperforate anus. He recovered quickly, was advanced on his diet, and was discharged to home on postoperative day 3. On postoperative day 5 following the stoma closure, he presented with an acute abdomen, pneumoperitoneum and an abdominal X-ray that revealed a 21 mm disc battery in the left lower quadrant. He underwent exploration and the battery was found perforating the anastomosis. There was significant fibropurulent exudate and inflammation. The battery was removed, the anastomosis was excised, and a colostomy with Hartman's pouch was performed. The toddler recovered uneventfully.This case offers an opportunity to discuss the concerns of battery ingestion and postoperative care following intestinal surgery in children. We could find no other similar reports in the world's literature of a disrupted colonic anastomosis due to battery ingestion.
Keywords: disc battery ingestion; colonic foreign body; colonic perforation; COVID-19